Trajectory of commercial establishments in Davao City - Yee, Philbert Fraser P. (UP in Mindanao, 2008)
This paper examines the overall trajectory of commercial establishments in Davao City by analyzing the spatial and temporal patterns for the service, producer, wholesaler and retailer and import-export categories in eleven(11) administrative districts from 1994 and 2000 to 2005 and factors that may have affected the trajectory of commercial development. The study utilized qualitative and quantitative approaches on the conduct of the research. The use of the case study approaches was also explored to confirm factors influencing location decisions of commercial establishments. Results show that the Central Business District (CBD) of Davao City is expanding and this trajectory is a manifestation of the theory of agglomeration and clustering. Conclusions of the study suggest that: (1) the existing spatial development strategy of the City Government towards the development of growth centers is not being realized; establishments will move away from the Poblacion but still within the vicinity and gravitate towards Talomo and Buhangin district; (2) there is a shift in the dominant type of commercial establishments in all districts from PWR to services; (3) the number of new commercial establishments and activities is increasing during the entire study period with upsurge noted between 2004 and 2005; and (4) the influence of population density to the type, intensity and location of commercial establishments is statistically significant In addition, case study findings show that infrastructure and settlement development patterns also exert significant influences to trajectory of commercial development. Study recommends the implementation of infrastructure projects particularly in the third Congressional District of Davao City where there is increasing number of commercial activities, and the conduct of review and enforcement of current zoning ordinances focusing on residential and commercial uses.